Patterns of multimorbidity and some psychiatric disorders: A systematic review of the literature - Castro-de-Araujo, Luis Fernando Silva; Cortes, Fanny; de Siqueira Filha, Noêmia Teixeira; Rodrigues, Elisângela da Silva; Machado, Daiane Borges; Araujo, Jacyra Azevedo Paiva de; Lewis, Glyn; Denaxas, Spiros; Barreto, Mauricio L. (Frontiers in Psychology, 2022)
Objective: The presence of two or more chronic diseases results in worse clinical outcomes than expected by a simple combination of diseases. This synergistic effect is expected to be higher when combined with some conditions, depending on the number and severity of diseases. Multimorbidity is a relatively new term, with the first fundamental definitions appearing in 2015. Studies usually define it as the presence of at least two chronic medical illnesses. However, little is known regarding the relationship between mental disorders and other non-psychiatric chronic diseases. This review aims at investigating the association between some mental disorders and non-psychiatric diseases, and their pattern of association. Methods: We performed a systematic approach to selecting papers that studied relationships between chronic conditions that included one mental disorder from 2015 to 2021. These were processed using Covidence, including quality assessment. Results: This resulted in the inclusion of 26 papers in this study. It was found that there are strong associations between depression, psychosis, and multimorbidity, but recent studies that evaluated patterns of association of diseases (usually using clustering methods) had heterogeneous results. Quality assessment of the papers generally revealed low quality among the included studies. Conclusions: There is evidence of an association between depressive disorders, anxiety disorders, and psychosis with multimorbidity. Studies that tried to examine the patterns of association between diseases did not find stable results. Keywords: multimorbidity, psychiatric disorders, clustering